Real‐time X‐ray imaging of mouse cerebral microvessels in vivo using a pixel temporal averaging method. (23rd December 2021) - Yu, Fucheng; Wang, Feixiang; Li, Ke; Du, Guohao; Deng, Biao; Xie, Honglan; Yang, Guoyuan; Xiao, Tiqiao
Abstract : A pixel temporal averaging method is developed to eliminate motion artifacts and random noises aiming at real‐time and in vivo radiology of mouse cerebral microvessels. Abstract : Rodents are used extensively as animal models for the preclinical investigation of microvascular‐related diseases. However, motion artifacts in currently available imaging methods preclude real‐time observation of microvessels in vivo . In this paper, a pixel temporal averaging (PTA) method that enables real‐time imaging of microvessels in the mouse brain in vivo is described. Experiments using live mice demonstrated that PTA efficiently eliminated motion artifacts and random noise, resulting in significant improvements in contrast‐to‐noise ratio. The time needed for image reconstruction using PTA with a normal computer was 250 ms, highlighting the capability of the PTA method for real‐time angiography. In addition, experiments with less than one‐quarter of photon flux in conventional angiography verified that motion artifacts and random noise were suppressed and microvessels were successfully identified using PTA, whereas conventional temporal subtraction and averaging methods were ineffective. Experiments performed with an X‐ray tube verified that the PTA method could also be successfully applied to microvessel imaging of the mouse brain using a laboratory X‐ray source. In conclusion, the proposed PTA method may facilitate the real‐time investigation of cerebral microvascular‐related diseases using small animal models.